Influence of Role Ambiguity and Conflicts on the Independence Commitment of Internal Auditor (Journal of Economic Research & Business Administration, 2021)
To increase the credibility of financial statements, an audit must provide documented reasonableassurance from an independent source that the financial statements provide a true and fair picture incompliance with an accounting standard. Independence is the freedom from circumstances which maylead to impartial conduct of the internal auditing functions. To maintain independence, auditors mustensure integrity and take an objective approach to the audit process. The auditor is required to carryout his or her task in a free and objective manner in accordance with the notion. The objective of thisstudy is to examine the influence of role ambiguity and conflict on the independence commitment ofinternal auditors of tertiary institutions in Osun State, Nigeria. The study population consists of the internalauditors of tertiary institutions in Osun State. The study selected sixty (60) internal auditors fromthe state-owned tertiary institutions to respond to the survey, using purposive sampling techniques.Multiple regression was conducted to analyse the data obtained. The study showed that role ambiguityand role conflict had a negative influence on the commitment of internal auditors to independence. Thefindings demonstrate, however, that the study’s projections are statistically validated. The results of thisstudy would provide empirical support for the reasons behind the resistant to independence commitmentamong internal auditors.Key words: Internal auditors, Independence commitment, Role ambiguity, Role conflict.